Influence of the quality of coronal restoration in the prognosis of endodontically treated teeth - Maricela Vallejo Labrada; Claudia Ximena Maya (Editorial Ciencias Médicas, 2015)
Introduction: the restoration of endodontically treated teeth is complex and controversial, and its prognosis is directly related to the quality of endodontic treatment and the final restoration, which should ensure a proper marginal seal to prevent coronary filtration and avoid subsequent endodontic failure. It has been shown that to handle badly a post-endodontic canal could cause failures for skiddingand microorganisms filtration which are found in the oral cavity and derived products to the apical portion of the root. Many factors during the endo-restorer treatment phase directly influence in its prognosis: apical sealant quality, residual amount of gutta-percha, early or late desobturation, sealing ability of the temporary or permanent restoration, disinfection canal among other. Objective: the purpose is to update professionals about clinical parameters to take into account in the rehabilitation of endodontically treated teeth, for this it is necessary to follow all the procedures under strict protocol and proper aseptic chain to prevent bacterial contamination. Methods: the literature search was conducted using the following terms coronal restoration, microfiltration, desobturation root, quality and endodontic status, articles that evaluated the effect of the quality of the root filling and coronal restoration or both in the success of a root canal were selected. Fifty-three articles were identified and reviewed by two investigators. Data were obtained from databases such as: Hinari, Science Direct, Wiley interscience, and indexed sources national and indexed sources national and international to predetermined criteria. Results: according to the concepts of infection control, all instruments and equipment placed inside the root canal must be sterile. Prevention of microfiltration is an important success endodontically treated tooth appearance, which must be rehabilitated in a short period of time between endodontics and final restoration to significantly reduce contamination. Conclusions: based on the available evidence, the results say that regardless of the technical or endodontic filling material or type of temporary or permanent restoration, is essential to maintain the aseptic chain along the whole treatment which added to an adequate final restoration promote the conservation sealed coronal y apical level to reduce the risk of bacterial.